Case Report: Everolimus reduced bone turnover markers but showed no clinical benefit in a patient with severe progressive osseous heteroplasia - Cebey-López, M.; Currás-Tuala, M. J.; Gómez-Rial, J.; Rivero-Calle, I.; Pardo-Seco, J.; Mendez-Gallart, R.; Pischedda, S.; Gómez-Carballa, A.; Barral-Arca, R.; Justicia-Grande, A.; Viz-Lasheras, S.; Rodríguez-Tenreiro, C.; et al. (Frontiers in Pediatrics, 2022)
Background. Progressive osseous heteroplasia (POH) is an ultra-rare genetic disorder characterized by an inactivating mutation in the GNAS gene that causes heterotopic ossification. Inhibition of mammalian target of rapamycin (mTOR) signalling pathway has been proposed as a therapy for progressive bone fibrodysplasia and non-genetic forms of bone heteroplasia. Herein we describe the impact of using Everolimus as rescue therapy of an identical twin girl suffering an aggressive clinical phenotype of POH. Methods. Clinical evaluation of the progression of the disease during Everolimus treatment was performed periodically. Cytokine markers involved in bone metabolism as well as protein markers related to the bone activity were analyzed to explore bone turnover activity. Results. The patient received Everolimus therapy for 36 weeks. During treatment, no clinical improvement of the disease was perceived. Analysis of biochemical parameters indicated that bone turnover activity was significantly reduced, namely β-CTX (r2 = −0.576, P-value = 0.016) and PNIP (r2 = −0.598, P-value = 0.011). Additionally, bone metabolism related biomarkers showed only a significant positive correlation with PTH levels. Conclusions. Everolimus treatment did not modify the clinical progression of the disease in an aggressive form of POH, although an impact in the protein markers studied was observed.